Interleukin-10 disrupts liver repair in acetaminophen-induced acute liver failure - Roth, Katherine; Strickland, Jenna; Pant, Asmita; Freeborn, Robert; Kennedy, Rebekah; Rockwell, Cheryl E.; Luyendyk, James P.; Copple, Bryan L. (Frontiers in Immunology, 2023)
Systemic levels of the anti-inflammatory cytokine interleukin 10 (IL-10) are highest in acetaminophen (APAP)-induced acute liver failure (ALF) patients with the poorest prognosis.The mechanistic basis for this counterintuitive finding is not known, as induction of IL-10 is hypothesized to temper the pathological effects of immune cell activation. Aberrant production of IL-10 after severe liver injury could conceivably interfere with the beneficial, pro-reparative actions of immune cells, such as monocytes. To test this possibility, we determined whether IL-10 levels are dysregulated in mice with APAP-induced ALF and further evaluated whether aberrant production of IL-10 prevents monocyte recruitment and/or the resolution of necrotic lesions by these cells. Our studies demonstrate that in mice challenged with 300 mg/kg acetaminophen (APAP), a hepatotoxic dose of APAP that fails to produce ALF (i.e., APAPinduced acute liver injury; AALI), Ly6C hi monocytes were recruited to the liver and infiltrated the necrotic lesions by 48 hours coincident with the clearance of dead cell debris. At 72 hours, IL-10 was upregulated, culminating in the resolution of hepatic inflammation. By contrast, in mice treated with 600 mg/kg APAP, a dose that produces clinical features of ALF (i.e., APAP-induced ALF; AALF), IL-10 levels were markedly elevated by 24 hours. Early induction of IL-10 was associated with a reduction in the hepatic numbers of Ly6C hi monocytes resulting in the persistence of dead cell debris. Inhibition of IL-10 in AALF mice, beginning at 24 hours after APAP treatment, increased the hepatic numbers of monocytes which coincided with a reduction in the necrotic area. Moreover, pharmacologic elevation of systemic IL-10 levels in AALI mice reduced hepatic myeloid cell numbers and increased the area of necrosis. Collectively, these results indicate that during ALF, aberrant production of IL-10 disrupts the hepatic recruitment of monocytes, which prevents the clearance of dead cell debris. These are the first studies to document a mechanistic basis for the link between high IL-10 levels and poor outcome in patients with ALF.